Kompetensi Kewirausahaan Kepala Sekolah - Putri Sasqia; Wahira Wahira; Sitti Habibah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study examines the description of the entrepreneurial competence of school principals at SMA Negeri 9 Makassar. This study aimed to determine the entrepreneurial competence of the principal in the school. This research approach is qualitative with a descriptive type of research in the form of written and oral documents from people or actors observed by the researcher—data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use the stages of data collection, data presentation, and concluding. From the results of the research, the principal's perception in reading and seeing developments in the surrounding educational environment, the forms of the principal's entrepreneurial competence, namely innovation and creativity competencies for the development of the principal school, innovate and ingenuity by building synergies with external and internal parties of the school which will have a good impact on the development of the school, especially school facilities and infrastructure outside of the boss's funds, Working hard for the development of his school where the principal always involves people who need his energy and thoughts in deliberation, Strong motivation the principal gives inspiration and encouragement to his subordinates to improve his performance which will affect his career in the future, Never give up the principal provides an understanding of the primary duties as a teacher and also the mentality of the principal in doing something to develop his school, never feel bored to correct what is still lacking in both teachers and students, the principal pays excellent attention to discipline and the principal constantly monitors all school activities, with the implementation of these indicators the principal has been able to produce successful entrepreneurs because successful entrepreneurs can be carried out if they have carried out these indicators.